Acute administration of interleukin‐6 does not increase secretion of glucagon‐like peptide‐1 in mice. Issue 13 (6th July 2018) - Christiansen, Charlotte B.; Lind, Sara J.; Svendsen, Berit; Balk‐Møller, Emilie; Dahlby, Tina; Kuhre, Rune E.; Hartmann, Bolette; Mandrup‐Poulsen, Thomas; Deacon, Carolyn F.; Wewer Albrechtsen, Nicolai J.; Holst, Jens J.
Abstract: Interleukin 6 (IL‐6) is a cytokine secreted from skeletal muscle in response to exercise which, based on animal and cell studies, has been suggested to contribute to glucose metabolism by increasing secretion of the incretin hormone glucagon‐like peptide‐1 (GLP‐1) and affecting secretion of insulin and glucagon from the pancreatic islets. We investigated the effect of IL‐6 on GLP‐1 secretion in GLP‐1 producing cells (GLUTag) and using the perfused mouse small intestine (harboring GLP‐1 producing cells). Furthermore, the direct effect of IL‐6 on insulin and glucagon secretion was studied using isolated perfused mouse pancreas. Incubating GLUTag cells with 1000 ng/mL of IL‐6 for 2 h did not significantly increase secretion of GLP‐1 whereas 10 mmol/L glucose (positive control) did. Similarly, IL‐6 (100 ng/mL) had no effect on GLP‐1 secretion from perfused mouse small intestine whereas bombesin (positive control) increased secretion. Finally, administering IL‐6 (100 ng/mL) to perfused mouse pancreases did not significantly increase insulin or glucagon secretion regardless of perfusate glucose levels (3.5 vs. 12 mmol/L glucose). Acute effects of IL‐6 therefore do not seem to include a stimulatory effect on GLP‐1 secretion in mice. Abstract : Interleukin 6 (IL‐6) is secreted during exercise and has been suggested to improve glucose homeostasis by stimulating secretion of glucagon‐like peptide‐1 (GLP‐1). Here, we show that IL‐6 does not acutely stimulates the secretion of GLP‐1 in mice. The benefical effect of IL‐6 on blood glucose therefore seems to be independent of GLP‐1.